Combined Direct and Indirect Cerebral Revascularization Using Local and Flow-Through Flaps - Azadgoli, Beina; Leland, Hyuma A.; Wolfswinkel, Erik M.; Bakhsheshian, Joshua; Russin, Jonathan J.; Carey, Joseph N. (Journal of Reconstructive Microsurgery, 2018)
Background Extracranial–intracranial bypass is indicated in ischemic disease such as moyamoya, certain intracranial aneurysms, and other complex neurovascular diseases. In this article, we present our series of local and flow-through flaps for cerebral revascularization as an additional tool to provide direct and indirect revascularization and/or soft tissue coverage.Methods A retrospective review of a prospectively maintained database was performed identifying nine patients. Ten direct arterial bypass procedures with nine indirect revascularization and/or soft tissue reconstruction were performed.Results Indications for arterial bypass included intracranial aneurysm (n = 2) and moyamoya disease (n = 8). Indications for soft tissue transfer included infected cranioplasty (one) and indirect cerebral revascularization (eight). Four flow-through flaps and five pedicled flaps were used including a flow-through radial forearm fasciocutaneous flap (one), flow-through radial forearm fascial flaps (three), and pedicled temporoparietal fascial (TPF) flaps with distal end anastomosis (five). The superficial temporal vessels (seven) and facial vessels (two) were used as the vascular inflow. Arterial bypass was established into the middle cerebral artery (six) and anterior communicating artery (three). There were no intraoperative complications. All flaps survived with no donor-site complications. In one case of flow-through TPF flap, the direct graft failed, but the indirect flap remained vascularized.Conclusion Local and flow-through flaps can improve combined direct and indirect revascularization and provide soft tissue reconstruction. Minimal morbidity has been encountered in early outcomes though long-term results remain under investigation for these combined neurosurgery and plastic surgery procedures.Level of Evidence The level of evidence is IV.
Keywords: EC-IC bypass; flow-through flaps; cerebral revascularization